The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1039/c9ra01337g
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic insight into the growth of calcia inclusions at the nanoscale: the case of Fe–O–Ca melt

Abstract: Thermodynamics of the formation of nano-CaO in liquid iron is important to explore the relationship between deoxidation reaction and size of inclusions, and is very useful in the size controlling of inclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…In addition, Wang et al 32 34 suggested that the thermodynamic of Al-deoxidation in liquid iron is closely related with the size of alumina. Xiao et al 35 37 reported that the deoxidation thermodynamics of metal in liquid iron have depended on the structures and properties of reaction products. Hence, it can be concluded that there is a close relationship between the thermodynamics of Al-deoxidaiton reaction in liquid iron and metastable phase, such nano-Al 2 O 3 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, Wang et al 32 34 suggested that the thermodynamic of Al-deoxidation in liquid iron is closely related with the size of alumina. Xiao et al 35 37 reported that the deoxidation thermodynamics of metal in liquid iron have depended on the structures and properties of reaction products. Hence, it can be concluded that there is a close relationship between the thermodynamics of Al-deoxidaiton reaction in liquid iron and metastable phase, such nano-Al 2 O 3 .…”
Section: Discussionmentioning
confidence: 99%
“…The initial structures of (Al 2 O 3 ) 2 cluster and α-Al 2 O 3 crystal were selected from the previous work 33 . The Gibbs free energy of (Al 2 O 3 ) 2 cluster and α-Al 2 O 3 crystal were calculated by the equations [33][34][35][36][37] where E is the total energy of alumina cluster or crystal at 0 K; H and S are the enthalpy and entropy of alumina cluster or crystal, respectively. The H and S were obtained by the analysis of atomic harmonic vibrational frequency of alumina cluster or crystal, which are the functions of temperature T. The calculation details of the relationship among the atomic harmonic vibrational frequency, the thermodynamic properties and temperature can be found in our previous study [33][34][35][36][37] .…”
Section: Theoretical Calculation Thermodynamic Modeling Of Nano-al 2 mentioning
confidence: 99%
See 2 more Smart Citations
“…where a C3A and a C12A7 are treated as pure substances based on Raoult's law, the activities of them are assumed to be 1. f Ca and f Al are the activity coefficients of Ca and Al in molten steel, respectively, which are calculated by Equation (11). The interaction coefficient e j i of Ca and Al has been summarized in Table 7 [41,44,45]. R is the ideal gas constant, which is 8.314 J/(mol•K).…”
Section: Thermodynamic Calculation Of [Al]-[ca] Equilibrium Of Liquid...mentioning
confidence: 99%